Severe declines in hydraulic capacity and associated carbon starvation drive mortality in seawater exposed Sitka-spruce (Picea sitchensis) trees. (1st March 2022) - Wang, Wenzhi; Zhang, Peipei; Zhang, Hongxia; Grossiord, Charlotte; Pennington, Stephanie C; Norwood, Matthew J; Li, Weibin; Pivovaroff, Alexandria L; Fernández-de-Uña, Laura; Leff, Riley; Yabusaki, Steven B; Waichler, Scott; et al.
Abstract: Sea-level rise is causing widespread tree mortality of coastal forests, with large consequences on the Earth system as a result of these forests' importance in carbon and nutrient export. The mechanisms of mortality under these conditions are, however, poorly tested. We used wood anatomy traits, wood δ 13 C, and tree radial growth to retrospectively assess the physiological process of seawater effects on whole tree xylem hydraulic capacity, gas exchange, and radial growth. During the latter stages of mortality (2018–2019), we directly measured metrics of water use and carbon metabolism across trees having crowns ranging from fully foliated to completely defoliated to investigate mortality processes at the sub-annual scale. Upon seawater exposure, soil salinity increased and allocation to hydraulic function declined, resulting in a dramatic reduction in water supply to the crown, increased crown-level water stress, and subsequent crown foliage loss. Simultaneously, leaf-level photosynthetic capacity declined steeply with increasing salinity. The combined loss of crown foliage area and photosynthetic rates per unit leaf area promoted carbon starvation, while no evidence of hydraulic failure was observed. These results elucidate mechanisms of coastal forest death under seawater exposure, enabling more accurate modeling in the future.